On Egypt's de facto Integration in the International Financial Market - Alnashar, Sara B. (Taylor and Francis, 2015)
This study explores whether Egypt has become de facto perfectly integrated in the international financial market following the steps taken towards the de jure liberalization of the capital and financial accounts of the balance of payments since the early 1990s. It does so by running two empirical tests, namely, the uncovered interest parity and the monetary autonomy tests using monthly data for the periods January 2000–December 2011 and July 2004–June 2008. The outcome of both tests indicates that during the periods under investigation, Egypt has maintained imperfect de facto integration in the international financial market, despite the de jure financial openness. To explore the reasons behind such imperfect de facto integration, the study estimates a vector error-correction model (VECM) using quarterly data for the period 2001/2002–2010/2011. According to the variance decompositions generated from the VECM, high inflation rate in Egypt has been a major contributor to the variability of the spread between interest rates on domestic and foreign financial assets, and thus could be deemed as a culprit behind Egypt's imperfect de facto integration.